Guiding Learning during the Pandemic Era to Encourage Learning Motivation of Talenta Delpita Orphanage’s Children - Sihombing, Christine; Suriadi, Agus (International Journal Labs, 2022)
Background: Learning assistance during the Covid-19 pandemic is a service to the community as one of the efforts to implement tri dharma college. Aim: This is done to increase students' learning motivation towards learning. Method: The learning mentoring method is done using the FGD method, namely Forum Group Discussion. This learning assistance is done in a small group of 6-12 people. Learning assistance is located at The Talenta Delpita Medan Orphanage. Before conducting learning assistance, the practice of doing several stages such as assasment to find out the problems that occur, then do planning and arranging activities before the implementation is carried out. The most important materials taught in this learning mentoring are reading, writing and basic mathematics. Findings: The learning assistance process runs smoothly and well. The results obtained from the mentoring of studying at The Talenta Delpita Medan Orphanage are very good. Children feel helped during this learning assistance process.